TRAINING AND GUIDANCE USING SPSS FOR TEACHERS’ RESEARCH DATA PROCESSING APPLICATIONS AT KECAMATAN TANGGETADA, KOLAKA SOUTHEAST SULAWESI - Ahmad Rustam; Sufri Mashuri (Universitas Sembilanbelas November Kolaka, 2016)
This devotion is aimed to improve the ability of teachers to process research data using SPSS. Things that the background is the lack of the use and knowledge of teachers in the use of SPSS and research works of teachers is lacking, one possible cause is the inability of teachers in data processing, especially using SPSS. This devotion includes four phases, namely, preparation, determination of the participants, the training and guidance of the use of SPSS, and direct practice of use of each of the steps in the data analysis in SPSS. The methods used include lectures and question and answer, targeted discussion groups, guidance and simulation data analysis, and direct practice with SPSS data analysis, and administration tasks. Outputs produced is yielding clues analysis work program SPSS for teachers and guidance techniques and operation of SPSS in data processing as well as the need to retrieve accurate results and capable operation of SPSS in data processing based on the instructions of work to be able to determine the valid data instrument and obtain accurate results.